Investigation of shoulder kinematics in volleyball spikes - Roemer, K.; Kuhlmann, C.; Milani, T. L. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
This study investigated the shoulder kinematics of volleyball spikes, performed during European League Games. For the kinematic description of the shoulder movement quaternions and the axis-angle approach was used to avoid the gimbal lock. The orientation of the resulting axis of rotation in the shoulder joint and the rotational angle were calculated. Additionally, the 3D coordinates of the elbow movement around the shoulder and the internal and external rotation were investigated. The results show that specific movement strategies for the humerus could be detected using these methods. Interdependencies of internal and external rotation with abduction and adduction were found for shoulder movements during volleyball spikes.